(untitled) (El-Wahat Journal for Research and Studies, 2025)
This study aimed to reveal the most important communication problems facing the teacher or learner, which hinder the good conduct of education. Therefore, this research paper sought to diagnose the communication situation at the Algerian school level, and try to find some effective solutions to enhance positive interaction between the teacher and his students, to achieve maximum benefit. Of the learning process. The survey method was adopted in this research paper, using the questionnaire as a tool for collecting data for a sample of 67 individuals in order to determine the achievement of the desired goal of this study. The most important results that we reached led to: The majority of the respondents confirmed that the teaching profession is a communication process between party’s .The educational process, and the obstacles that the process of communication between parties in the educational process contributes to the student’s involvement in building the lesson, which is controlled by nature if the language used for teaching. Keywords: communication, communication problems, teacher, learner, school, Algerian school